Aplikasi Metode Quantum Dengan Model Pembelajaran Tipe Circ Pada Materi Pythagoras Terhadap Hasil Belajar Siswa - Kamal Fahlevi (Program Studi PGSD Kampus UPI di Serang, 2020)
Mathematics is one of the subjects that are included in the national exam and is still considered difficult by students. Results in the field show that student learning outcomes on the last semester exam in mathematics are still below the minimum completeness criteria. it is necessary to apply certain models and methods, one of which is the Quantum Learning Method, the Quantum Method is a method, instructions, strategies, and the entire learning process that can sharpen understanding and memory, and make learning a fun and useful process. In this study, the Quantum Method is collaborated with one of the learning models known as the CIRC type of cooperative learning model. This study aims to determine the learning outcomes of class VIII students of MTsS Ulumul Qur'an using the quantum method with the CIRC cooperative learning model in the Pythagorean material. Data obtained through test instruments, observation and interviews. Based on the research results, it was found that in the first cycle, the percentage of students who got a score of ≥ 70 was 42.46%, and had not reached the KKM 80%. Then in the second cycle the percentage of students who scored ≥ 70 was 82.76%. So the results of the second cycle research can be said to be successful because it has reached the KKM 80%.